200 Years of Lithium and 100 Years of Organolithium Chemistry - Wietelmann, Ulrich (Z Anorg Allg Chem, 2018)
The element lithium has been discovered 200 years ago. Due to its unique properties it has emerged to play a vital role in industry, esp. for energy storage, and lithium‐based products and processes support sustainable technological developments. In addition to the many uses of lithium in its inorganic forms, lithium has a rich organometallic chemistry. The development of organometallic chemistry has been hindered by synthetic problems from the start. When Wilhelm Schlenk developed the basic principles to handle and synthesize air‐ and moisture‐sensitive compounds, the road was open to further developments. After more information was available about the stability and solubility of such compounds, they started to play an essential role in other fields of chemistry as alkyl or aryl transfer reagents.